Kompetensi Strategis Matematis Pada Materi Bangun Ruang Sisi Datar - Restriani Utami; Jarnawi A. Dahlan (Didactical Mathematics, 2023)
This study aims to examine the mathematical strategic competency abilities of junior high school students in the material of faces three-dimensional geometry. The type of research used is quantitative descriptive research. The population in this study were class IX students at one of the Bandung City Public Middle Schools. The selection of samples using purposive sampling technique, obtained by class IX students as many as 27 students. Data was collected with instruments in the form of students' strategic competence ability tests in the form of written essay tests that have been validated theoretically. Data analysis was carried out quantitatively both as a whole and results based on indicators on strategic competency abilities. The results showed that the students' strategic competency skills in the faces three-dimensional geometry material were included in the low category. Based on the indicators, the achievement of formulating the problem is in the sufficient category, while the achievement of representing the problem in the form of a mathematical model and solving the problem is still in the less category.